“Evaluación de tres tipos de abonos orgánicos en la producción de la papa (Solanum tuberosum) variedad chaucha en el Cantón Ambato Provincia de Tungurahua.”. - Yucailla Baltazar, María Manuela (2020)
The potato is one of the main foods that has spread the most in its production, occupying the seventh place of production at the national level, the purpose of this research is to obtain a product free of contaminants: This project was carried out in Ambato, Province of Tungurahua, The objectives set out in this research were the following: To evaluate the agronomic response of three types of organic fertilizers in the "Chaucha" potato crop, to determine the percentage that it can generate in the "Chaucha" potato production. The Design of Blocks Completely Random was made with the application of 5 treatments with 5 repetitions. The application of different organic fertilizers was carried out in doses of 4 kg of guinea pig manure, 3 kg of chicken manure, 4 kg of humus, 1 kg of solid fertilizer and the control, the following results are presented below: in plant height the best treatment at 120 days was treatment 4 with doses of 1kg of solid fertilizer, while in the variable number of tubers it was in treatment 1 with doses of 4 kg of guinea pig manure with 83 units of tubers, in the variable weight by treatment, the best result obtained in treatment 4 with doses of 1 kg of solid fertilizer obtained 49.07 kg, in the benefit / cost variable, the best results were obtained in treatment 4 and the control with values of 1.15 and 1, 16 USD respectively, the values obtained by organic fertilizers were not satisfactory since the crop at the time of the investigation had problems due to the attack of the disease called purple top.